If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 15) = 45 + 12x Reorder the terms: (15 + 4x) = 45 + 12x Remove parenthesis around (15 + 4x) 15 + 4x = 45 + 12x Solving 15 + 4x = 45 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 15 + 4x + -12x = 45 + 12x + -12x Combine like terms: 4x + -12x = -8x 15 + -8x = 45 + 12x + -12x Combine like terms: 12x + -12x = 0 15 + -8x = 45 + 0 15 + -8x = 45 Add '-15' to each side of the equation. 15 + -15 + -8x = 45 + -15 Combine like terms: 15 + -15 = 0 0 + -8x = 45 + -15 -8x = 45 + -15 Combine like terms: 45 + -15 = 30 -8x = 30 Divide each side by '-8'. x = -3.75 Simplifying x = -3.75
| 24*5v/8 | | y/-6=-10 | | -5=14x | | x^3-x^2=36 | | 9p=54iswhat | | 5(x/4)=7(x-2) | | 4+x+2-2=5 | | 4(2x-5)=3(x+10)-15 | | x^2+8x-731=0 | | 2n/-6 | | 30x/5x= | | 2b+6=3b+6 | | 3=18/x-18 | | x^3/x= | | 3[0.2x+(-2)]= | | 13x-2x-3x=66 | | 6x(x-1)+13=7 | | 1/14(0-8)-9 | | g(b+6)=3x-1 | | 3b^3+9b^2= | | 8(w-6)-(7-4w)=11w | | 8x=20/75 | | 3x/5=-4/9 | | (X^2+1)(x^4-2x^3-5x^2-6x)=0 | | -6w+12=42 | | -9=1-5w | | 28x^2-61+21=0 | | -29=4w-9 | | -11-3y=7 | | 4(2y+1)=34 | | 4x+-3(x+5)=10 | | 2x(-3x+5)=6 |